Akkád nyelvű "magan"-feliratok as i.e. első évezredből. Szövegkritika és történeti elemzés - Háklár, Noémi (1980)
MA Thesis; Supervisor: G. Komoróczy; Akkadian "Private" Inscriptions of the First Millennium B.C. Textual Criticism and Historical Analysis; inscriptions of Nergal-ēreš (Tell al-Rimah and Saba'a); Šamši-ilu (RA 27,1 Iff.); Bēl-Ḫarrān-bēla-uṣur (RT 16, 176 ff.); Šamaš-rēša-uṣur (Weissbach, WVDOG 4, No. 4; KAH 2, No. 26); Sebettu-rēmēni (KAH 2, No. 138); Mušēzib-Šamaš (Pognon, Inscriptions, 106ff.)